The unusually colourful 'clothing' changes of Lepidophorella australis Carpenter, 1925 (Collembola: Tomoceridae). Issue 1 (2nd January 2017) - Hawes, Timothy C.
ABSTRACT: Colour changing is a well-known phenomenon exhibited by a number of terrestrial arthropods. Non-random 'morphing' of the visible phenotype has generally been associated with changes in response to the environment. This article describes a previously unrecognised class of colour change which occurs as a result of endogenous rather than exogenous changes: specifically, moulting. The tomocerid springtail Lepidophorella australis dramatically changes its colour phenotype from silver-grey to yellow and back again during its moult cycle. These colour changes are caused by alternations between structural colouration (conferred by its 'clothing' of scales) and cuticular pigmentation during ecdysis (scale loss) and post-ecdysis (scale regeneration). Although the rate and frequency of change is affected by external factors related to development (e.g. temperature), it is a fixed component of life history. The extent of the difference between colour phenotypes means that they produce distinctly different visual (and presumably, therefore, ecological) signals. It is hypothesised that bright yellow subscale pigmentation may operate as a signal of aposematism when L australis are vulnerable to predation as a result of reduced activity and absent cuticular scales.